Utility of anti-carbamylated protein antibodies in the diagnosis of early rheumatoid arthritis - Ashraf H Mohamed; Asmaa Enein; Noha Abdelsalam; Mona Balata; Sameh Abdellatif; Ehsan Rizk; Ahmed Fathy (Indian Journal of Rheumatology)
Background: Anti-carbamylated protein (anti-CarP) antibodies are present in patients with Rheumatoid arthritis (RA) and may present before disease onset. Our aim is to investigate the diagnostic value of anti-CarP antibody in Egyptian RA patients. Methods: This cross-sectional study included 96 RA patients (56 patients with early disease and 40 patients with established disease) and 60 healthy controls. Demographic and clinical data, smoking status, and disease activity score were recorded. Laboratory tests included erythrocyte sedimentation rate, C-reactive protein, rheumatoid factor, anti-citrullinated protein antibodies, and anti-CarP antibody. Results: Anti-CarP antibody levels in RA patients were significantly higher than in controls (8.80 ± 5.95 vs. 2.19 ± 1.01, P < 0.0001). Out of 96 RA patients; 74 (77.1%) were positive for anti -CarP anti body including 47patients with early RA while only 5 subjects (8.3%) in control group were positive. Receiver-operating characteristic curve study for diagnostic efficacy of anti-CarP antibody in early RA diagnosis demonstrated a significant area under the curve, 0.950 (95% confidence interval, 0.912–0.987, P < 0.0001) and yielded a sensitivity of 85.4%, a specificity of 93.3%, a positive predictive value of 0.90, and a negative predictive value of 0.86. Conclusion: Anti-CarP antibody is a useful biomarker for early RA diagnosis.